EFEKTIVITAS PENGELOLAAN DANA DESA DI DESA KALINAUN KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA - KAWOWODE, OLIVIA; TAMPI, GUSTAAF BUDI; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: The realization of village funds is a follow-up to the government’s program of building Indonesia from the periphery by strengthening the regions and villages within the framework of the Unitary State of the Republic of Indonesia aimed at improving the welfare and equity of development through improving public services, promoting the economy, overcoming the inter-village development gap and strengthening the community as subject of development. The purpose of this study is to determine the extent of effectiveness of village fund management in Kalinaun Village, East Likupang District, North Minahasa District. This research is a descriptive research with qualitative approach. Technique of collecting data in this research is using observation method that is direct observation to research location and do interview and documentation. The focus of research is the achievement of goals, integration and adaptation. Based on the results of the research, the effectiveness of the management of village funds in Kalinaun Village, East Likupang District, North Minahasa Regency, can not be said to be effective because the development done by the government still finds some problems and the development is not done evenly, making social jealousy among the community. The Kalinaun Village Government is also inconsistent with what it deliberates so that people are reluctant to work together. Keywords: Effectiveness of Village Fund Management.